Pengaruh Pajak Hotel, Restoran Dan Hiburan Terhadap Pad Kabupaten Belitung - Viny Widiani, Ngadiman (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This study is aimed to find out the influence of Hotel Tax, Restaurant Tax and Entertainment Tax versus The Original Regional Revenue on period 2008 until 2019. This study is carried out in the local tax offices and financial management of Belitung Districts. The type of this research was case study with interview and documentation as the data collecting techniques, in this study also used a sample taken from the percentage data of the realization of financial statements in 12 (twelve) years on period 2008 until 2019 with 12 data as the total. The data analysis technique was multiply regression analysis using SPSS 25 program with quantitative research methods and descriptive approaches at 5% significance level. The result of regression analysis showed that there were simultaneous and significantly influenced among of Hotel Tax, Restaurant Tax and Entertainment Tax versus The Original Regional Revenue of Belitung Districts period 2008 to 2019. The implication of this study is the realization of regional tax revenue can reach the predetermined target and that local tax collection can be carried out more effectively and efficiently to support regional development in Belitung Districts.